A low-cost output terminal for time-shared computers - Rosenberg, Ronald C.; Kennedy, Daniel W.; Humphrey, Roger A. (Project MAC, Mass. Inst. of Technology, 1967)
A low cost remote terminal which provides output in switch form from a time-shared digital computer is described. The terminal consists of a modified model 35 KSR teletype and a local memory unit. The unit is independent of the particular computer, and is easy to test and maintain. The states of the memory control and memory words are observable directly by indicator lights. An application of the memory to the automatic set-up and control of an analog computation are displayed on an oscilloscope; this makes possible, for example, the rapid display of time response of linear systems, under digital program control. (Author).
Als Kopie ersch. bei d Arbeitsstelle für Reprotechnik im Inst. für Dokumentationswesen
Keywords: Analog systems; Communication and radio systems; Computer Hardware; Computer Systems; Digital computers; Display systems; Input output devices; Real time; Remote control; Time sharing; Wiring diagrams; Peripheres Gerät; Drucker -- Datentechnik